Adolescents’ smoking environment under weak tobacco control - SILNE-R Group (2019)
Introduction: Bans on smoking in public places and on sales to minors have been widely implemented across the globe. However, many countries have either adopted non-comprehensive (i.e., partial) bans and/or weakly enforce those bans. Little is known, from the adolescents’ perspective, how this affects their smoking-related perceptions and behaviors. We studied the case of Portugal, where bans are partial and/or weakly enforced. We sought to understand how the bans affect adolescents’ access to cigarettes from commercial sources, the visibility of smoking in public places, and smoking locations. Material and methods: We used a mixed methods design on data gathered in 2016. Quantitative, cross-sectional surveys were conducted in six schools (n = 2,444) in Coimbra, Portugal. In two of these schools, qualitative data were collected in eight single-sex focus group interviews (n = 42). Results: Ninety-five percent of the adolescents who tried to buy cigarettes were able to do so from commercial sources, through vending machines, or directly from the vendor. Bans on smoking on school premises and at enclosed public places did not prevent these adolescents from observing smoking outside school gates (84.0%), in cafes and restaurants (97%), or from smoking at cafes, bars, or nightclubs (72.9%). Discussion: Partial and/or weakly enforced policies seem to not prevent adolescents from having access to cigarettes, frequently seeing smoking, and finding ample opportunities to smoke in public places. Adopting and enforcing comprehensive policies are necessary efforts to prevent unfavorable responses and more effectively reduce adolescents’ smoking behavior.